PELAYANAN ADMINISTRASI DAN KEPUASAN PUBLIK: Studi Kasus Dinas Kependudukan dan Catatan Sipil Kota Kendari - Adrian Tawai; La Ode Muhammad Elwan; La Ode Muh. Munadi (Halu Oleo University, 2025)
The Population and Civil Registry Service provides various services such as making Resident Identity Cards, Family Cards, birth certificates, death certificates and other population documents. This research specifically evaluates the extent to which the services provided by the Kendari City Population and Civil Registry Service meet community expectations, using a survey that includes speed of service, accuracy of data, friendliness of officers, ease of access to information, and supporting facilities. The results of the research show that there are still several problems related to speed of service (14,5% or 29 respondents strongly disagree), data accuracy (8,5% or 17 respondents strongly disagree), and friendliness of officers (19% or 38 respondents strongly disagree). agree), easy access to information (10,5% or 21 respondents strongly disagree), and adequate supporting facilities (5,5% or 11 respondents strongly disagree). This research concludes that the Kendari City Population and Civil Registry Service must continue to improve service quality by making it more transparent and accountable.